2015
DOI: 10.1007/s00265-015-1918-9
|View full text |Cite
|
Sign up to set email alerts
|

Lazy males and hardworking females? Sexual conflict over parental care in a brood parasite host and its consequences for chick growth

Abstract: Due to the costs of parental care, a conflict of interests often arises between mates wherein each prefers the other to invest more. As with parents raising their own offspring, hosts of brood parasites also exhibit negotiations over investment, becoming particularly intensive when parasite demands are high. Lack of cooperation between the partners may eventually affect the condition and fledging success of the young. Here, we investigate the magnitude of sexual conflict over food provisioning in socially poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Although breeding with polygynous males is more demanding for females due to lower male investment in nestling care (e.g. Lundberg and Alatalo 1992;Huk and Winkel 2006;Požgayová et al 2015), fledging success of own chicks and brood parasitism perhaps play a more important role in determining female return rate. The association of the focal breeding parameters with return rates and dispersal distances did not vary for different study years.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although breeding with polygynous males is more demanding for females due to lower male investment in nestling care (e.g. Lundberg and Alatalo 1992;Huk and Winkel 2006;Požgayová et al 2015), fledging success of own chicks and brood parasitism perhaps play a more important role in determining female return rate. The association of the focal breeding parameters with return rates and dispersal distances did not vary for different study years.…”
Section: Discussionmentioning
confidence: 98%
“…Female investment to breeding is larger than those of (often polygynous) males (Trnka and Grim 2013;Požgayová et al 2015), and hence, the prolonged care for a cuckoo chick could be much more demanding for host females than males. Subsequently, increased stress during breeding might lower female chances to prepare properly for migration and potentially raise their mortality.…”
Section: Discussionmentioning
confidence: 99%
“…As we were focused on cuckoo state closely to the time of falling‐out of the nest, we counted all parental feeding visits during the three‐hour time span preceding the cuckoo chick falling‐out. In the successful nests, we analysed feeding visits from video‐recordings in which the cuckoo chicks were of the same age as in those in assigned unsuccessful nests and from the same time because the behaviour of parents could depend on both nestling age and daytime (Požgayová et al ). As one unsuccessful nest was excluded from the analysis because the quality of recording was not sufficient to count parental feeding visits, the final dataset comprised of 15 successful and 15 unsuccessful nests.…”
Section: Methodsmentioning
confidence: 99%
“…We explore the relative role of males and females in provisioning in a context of parasitism. As a consequence of the lower brood size in parasitized nests (Methods), 2) we expect that males should reduce their provisioning rates as it has been found in other hosts (Požgayová et al 2015). Finally, to identify possible long-term consequences of raising parasitic nestlings for hosts, we investigate whether parasitism status and magpie provisioning rates in a breeding attempt can influence its presence in the breeding population and its breeding phenology in the subsequent breeding season.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, brood parasitism could also affect the relative parental contribution of males and females, for example, by affecting brood size (Komdeur et al 2002), a possibility seldom explored. For example, Požgayová et al (2015) found that males work less in great reed warbler Acrocephalus arundinaceus nests parasitized by the common cuckoo Cuculus canorus than in non-parasitized nests, even in monogamous pairs, which constitute an important part of the population. Contrastingly, red-winged blackbird Agelaius phoeniceus nests parasitized by the brownheaded cowbird Molothrus ater were more likely to receive care from the male than non-parasitized nests (Grayson et al 2013).…”
Section: Introductionmentioning
confidence: 99%